Molecular dynamics study of Pseudomonas aeruginosa lectin-II complexed with monosaccharides - Mishra, Navnit Kumar; Kulhánek, Petr; Snajdrová, Lenka; Petrek, Martin; Imberty, Anne; Koca, Jaroslav (Proteins, 2008)
We present the results of a series of 10-ns molecular dynamics simulations on Pseudomonas aeruginosa lectin-II (PA-IIL) and its complexes with four different monosaccharides. We compare the saccharide-free, saccharide-occupied, and saccharide- and ion-free forms of the lectin. The results are coupled with analysis of the water density map and calcium coordination. The water density pattern around the binding site in the free lectin molecular dynamics was fitted with that in the X-ray and with the hydroxyl groups of the monosaccharide within the lectin/monosaccharide complexes and the best ligand was predicted based on the best fit. Interestingly, the water density pattern around the binding site in the uncomplexed lectin exactly fitted the O2, O3, and O4 hydroxyl groups of the fucose complex with the lectin. This observation could lead to a hypothesis that the replacement of these three water molecules from the binding site by the monosaccharide decreases the entropy of the complex and increases the entropy of the water molecules, which favors the binding. It suggests that the high density peaks of the solvent around the binding site in the free protein could be the tool to predict hydroxyl group orientation of the sugar in the protein/sugar complexes. The high affinity of PA-IIL binding site is also attributed to the presence of two calcium ions, each of them making five to six coordinations with the protein part and two coordinations with either water or the monosaccharide. When the calcium ions are removed from the simulated system, they are replaced by sodium ions from the solvent. These observations rationalize the high binding affinity of PA-IIL towards fucose.
Keywords: Computer Simulation; Monosaccharides; Calcium; Models, Molecular; Temperature; počítačová simulace; konformace sacharidů; kyslík; Oxygen; lektiny; Protein Structure, Secondary; Carbohydrate Conformation; vazebná místa; Pseudomonas aeruginosa; vápník; voda; monosacharidy; Binding Sites; Water; molekulární modely; sekundární struktura proteinů; teplota; Lectins